Efficiency Analysis of Zakat Distribution on Interprovincial Human Development Index In Digital Era - Arsyi, Muhammad; Akbar, Nashr (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2025)
This study aims to evaluate and analyze the efficiency of zakat distribution per province in Indonesia from 2020 to 2023 towards the achievement of the Human Development Index (HDI). The variables used in this research are zakat distribution on sectors (Education, Health and Economy) as input variable and HDI indicator as output variable. In addition, the determinants of efficiency are also further analyzed to find factors that can be optimized to improve the level of efficiency. This research uses Data Envelopment Analysis (DEA) Bootstrapping to measure the relative efficiency of zakat distribution per province In Indonesia, this research investigates how effective zakat is in improving human development outcomes in Indonesia The findings are expected to identify high and low performing provinces in zakat management, as well as provide insights and policy recommendations to improve zakat distribution strategies and optimize its socio economic impact, especially in the context of poverty alleviation and regional development in Indonesia.